INTERNAL REVENUE ALLOTMENT: THE CASE OF BARANGAY CALAMBA, CEBU CITY - U. Gulane , Ian Rovii; C. Viray , Marecon (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2024)
This study focused on exploring the knowledge level of awareness and implementation of the Internal Revenue Allotment in BarangayCalamba, Cebu City. It sought to determine the answer 1. What is the demographic profile of the respondents, 2. What is the level of awareness of the respondents towards internal revenue allotment? 3. What are the strategies used by the BarangayCaptain in collecting internal revenue allotment and its levelof implementation? 4. What is the perception of the respondents on the contribution of the collected Real Property Tax to the operation of BarangayCalamba? The research design used was descriptive, that is by employing percentage distribution and frequency counts in presenting and analyzing the data obtained from a sample of fifty-eight (58) respondents. A validated researcher-made questionnaire was used to collect the primary data. The findings on this study revealed there was a Barangaydevelopment plan; however, budget allocation is the problem observed, and these plans were not fully implemented.With those problems, this paper suggests that education be given importance, it is recommended that Barangaypersonnel and authorities participate in an integrated capacity-building program. Educating people on practical issues such as dealing with the administration of IRA towards development, not only the officials but most importantly, the residents or the ordinary people too, so that they will be able to participate and contribute to their own development.